Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Select the correct answer.

Solve the following inequality for [tex]$x$[/tex].

[tex] x - 9 \leq 2(9 - x) [/tex]

A. [tex] x \leq 9 [/tex]

B. [tex] x \geq 11 [/tex]

C. [tex] x \ \textless \ -7 [/tex]

D. [tex] x \ \textless \ 10 [/tex]


Sagot :

Let's solve the inequality step-by-step:

Given inequality:
[tex]\[ x - 9 \leq 2(9 - x) \][/tex]

1. Distribute the 2 on the right side of the inequality:
[tex]\[ x - 9 \leq 2 \cdot 9 - 2 \cdot x \][/tex]
[tex]\[ x - 9 \leq 18 - 2x \][/tex]

2. Combine like terms by adding [tex]\(2x\)[/tex] to both sides:
[tex]\[ x + 2x - 9 \leq 18 \][/tex]
[tex]\[ 3x - 9 \leq 18 \][/tex]

3. Isolate the term [tex]\(3x\)[/tex] by adding 9 to both sides:
[tex]\[ 3x - 9 + 9 \leq 18 + 9 \][/tex]
[tex]\[ 3x \leq 27 \][/tex]

4. Divide both sides of the inequality by 3:
[tex]\[ x \leq \frac{27}{3} \][/tex]
[tex]\[ x \leq 9 \][/tex]

Therefore, the correct answer is:
[tex]\[ A. \ x \leq 9 \][/tex]